ECTOPARASITES ASSOCIATED WITH THE GILLS OF THE ARAHUANA, Osteoglossum bicirrhosum (Cuvier, 1829) FROM THE LAKE EL DORADO (PACAYA SAMIRIA NATIONAL RESERVE), PERUVIAN AMAZON - BIFFI GARCÍA, Claudia (2018)
The objective of this study was to determine the diversity and abundance of ectoparasites in the gills of 80 specimens of Arahuana Osteoglossum bicirrhosum (Cuvier, 1829) from Lake “El Dorado” in the Pacaya-Samiria National Reserve, in Loreto, Peru. The gills of each specimen were collected and placed separately in formalin and water solution (1: 4000) and preserved in refrigeration at 4 °C until laboratory analysis. The analysis consisted of the location, counting, collection and fixation of the ectoparasites of each branchial arch. The results showed that 100% of the analyzed specimens were infested with one or more ectoparasites. A total of five species of Monogenoidea were identified: Gonocleithrum cursitans Kritsky & Thatcher, 1983, Gonocleithrum aruanae Kritsky & Thatcher, 1983 and Gonocleithrum coenoideum Kritsky & Thatcher, 1983 and two Copepoda: Ergasilus sp. and Therodamas elongatus (Thatcher, 1986). Gonocleithrum cursitans was the ectoparasite with the highest prevalence (100%). Therodamas elongatus is reported for the first time in Peru, parasitizing specimens of O. bicirrhosum.